2011
DOI: 10.5005/jp-journals-10017-1008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Anakinra for the Treatment of Persistent Inflammation and Arthrofibrosis following Anterior Cruciate Ligament Reconstruction

Abstract: Purpose: Postoperative inflammation and arthrofibrosis remain difficult problems following ACL reconstruction. Interleukin-1 (IL-1) is a potent driver of intra-articular inflammation and arthrofibrosis following injury and surgery. Anakinra (Kineret, Amgen, Thousand Oaks, CA) is an IL-1 receptor antagonist. We hypothesize that postoperative intra-articular anakinra use decreases inflammation and subsequent arthrofibrosis, reducing the need for arthroscopic debridement and manipulation under anesthesia.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In patients with arthrofibrosis after ACLR, intra-articular injection of the IL-1 antagonist anakinra improved the ROM. 15 Fibroblasts produce extracellular matrix and their proliferation is an important process in the formation of arthrofibrosis. 33,34 Fibroblasts isolated from the synovium express high levels of the IL-1 receptor 35 and proliferate in response to IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with arthrofibrosis after ACLR, intra-articular injection of the IL-1 antagonist anakinra improved the ROM. 15 Fibroblasts produce extracellular matrix and their proliferation is an important process in the formation of arthrofibrosis. 33,34 Fibroblasts isolated from the synovium express high levels of the IL-1 receptor 35 and proliferate in response to IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies suggested that postsurgery inflammation triggers the formation of arthrofibrosis, 11,13 and antiinflammatory treatments with corticosteroids or interleukin-1 (IL-1) receptor antagonists improved the range of motion (ROM) in patients with ACLR-induced arthrofibrosis. 14,15 However, the details of the formation processes of arthrofibrosis are unknown. Elucidation of the time-dependent changes in inflammatory and fibrotic reactions after ACLR will help to guide the optimal timing of antiinflammatory/antifibrotic treatments.…”
Section: Introductionmentioning
confidence: 99%